2016
DOI: 10.1186/s40886-016-0050-5
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related problems and their clinical interventions in a Ghanaian teaching hospital

Abstract: Background: Errors occur frequently in the use of medicines. Pharmacists play a key role in error identification and make appropriate interventions as they work with other healthcare professionals. These error recovery roles of pharmacists contribute to patient safety. This study was to evaluate the clinical interventions made to drug-related problems at a tertiary care setting. Method: This involved a retrospective review of clinical intervention reports submitted by pharmacists working over the period Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…This type of error occurred mainly due to pen writing habits of the physician. Our study regarding prescribing error identification coincides with Acheampong F (2016) 17 where they reported that, majority of drug errors were due to Prescription habit. Our study identified Drug duplication as another major MRP.…”
Section: Drug Insufficiencysupporting
confidence: 87%
“…This type of error occurred mainly due to pen writing habits of the physician. Our study regarding prescribing error identification coincides with Acheampong F (2016) 17 where they reported that, majority of drug errors were due to Prescription habit. Our study identified Drug duplication as another major MRP.…”
Section: Drug Insufficiencysupporting
confidence: 87%
“…This result was comparable with studies carried out in Southern India and Karnataka, India, which revealed that clinical pharmacists' acceptance was about 97% and 96%, respectively [ 36 , 37 ]. Moreover, a study carried out in Ghana, South Western Saudi Arabia, Northern Cyprus, and India showed that clinical pharmacists' intervention and acceptance rates were about two-thirds of the study population [ 38 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acheampong et al have shown similar findings in Ghana. 19 In a prospective study of heart failure patients at a teaching hospital in Ethiopia, Niriayo et al reported anticoagulants among the drugs most frequently implicated in DRPs. 27 A review of DRPs has shown that the use of anticoagulants is associated with a higher occurrence of DRPs.…”
Section: Acceptance and Implementation Of Pharmacists' Interventions ...mentioning
confidence: 99%
“…26 Although antibiotics have been found to be frequently implicated in DRPs, 20 cardiovascular drugs including blood pressure lowering medicines, statins, and antithrombotics have also shown a potential to frequently account for DRPs. 19,23,27,34 Furthermore, the number of drugs prescribed, demographic factors such as age and sex, drugs with a narrow therapeutic index, or renal elimination are likely to influence the frequency of DRPs. 19,23,25,34 Although DRPs are likely to occur in cardiovascular disease patients, 27,29,35 the frequency and type of DRPs are likely to vary depending on the method used to detect errors or ADRs (systematic screening of patients vs. chart review or spontaneous reporting) and the clinical departments or wards where studies are conducted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation